Retained Bullets After Firearm Injury: A Survey on Surgeon Practice Patterns. Issue 1 (January 2022) - Smith, Randi N.; Tracy, Brett M.; Smith, Stephanie; Johnson, Sean; Martin, Niels D.; Seamon, Mark J.
Retained bullets are common after firearm injuries, yet their management remains poorly defined. Surgeon members of the Eastern Association for the Surgery of Trauma ( N = 427) were surveyed using an anonymous, web-based questionnaire during Spring 2016. Indications for bullet removal and practice patterns surrounding this theme were queried. Also, habits around screening and diagnosing psychological illness in victims of firearm injury were asked. Most respondents were male (76.5%, n = 327) and practiced at urban (84.3%, n = 360), academic (88.3%, n = 377), Level 1 trauma centers (72.8%, n = 311). Only 14.5% ( n = 62) of surgeons had institutional policies for bullet removal and 5.6% ( n = 24) were likely to remove bullets. Half of the surgeons (52.0%, n = 222) preferred to remove bullets after the index hospitalization and pain (88.1%, n = 376) and a palpable bullet (71.2%, n = 304) were the most frequent indications for removal. Having the opportunity to follow-up with patients to discuss bullet removal was significantly predictive of removal (odds ratio (OR) = 2.25, 95% confidence interval (CI) = [1.05, 4.85], p = .04). Furthermore, routinely asking about retained bullets during outpatient follow-up was predictive of new psychological illness screening (OR = 1.94, 95% CI [1.19, 3.16], p = .01) and diagnosis (OR = 1.86, 95% CI = [1.12, 3.09], p = .02) in victims of firearm injury. Thus, surgeons should be encouraged to allot time for patients concerning retained bullet management so that a shared decision can be reached.